PENINGKATAN SIKAP MANDIRI DAN HASIL BELAJAR MATERI PERKALIAN DAN PEMBAGIAN MENGGUNAKAN MODEL PBL SISWA KELAS IV SDN JONGKANG - Galih Kinanti, Yosefine; Purnomo, Puji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was inspired by the low level of independence and learning outcomes of fourth-grade students at Jongkang State Elementary School in the 2025/2026 academic year, as obtained from interviews, observations, and questionnaires. This study aims to improve the independence and learning outcomes of fourth-grade students at Jongkang State Elementary School in multiplication and division using the PBL model. This research was a classroom action research (CAR). The subjects of this research are fourth-grade students at Jongkang State Elementary School in the 2025/2026 academic year. Data collection techniques were obtained through observation, questionnaires, interviews, and tests. The data analysis technique used in this study is quantitative descriptive. The results of this study shows that 1) The application of the PBL model, which was implemented through problem-solving steps, was able to improve the independence and learning outcomes of fourth-grade students at Jongkang State Elementary School in multiplication and division. 2) The use of the PBL model can improve students' independent attitudes with an average of 41.21 at the initial stage, to 57.79 in cycle I, and increasing to 78.97 in cycle II. 3) The use of the PBL model can improve students' independent attitudes with an average score of 59.39 with a mastery level of 39.28% at the initial stage, increasing to 65.95 with a mastery level of 60.71% in cycle I, and further increasing to 76.78 with a mastery level of 82.18% in cycle II. 4) The use of the PBL model was effective in improving students' independent attitudes and learning outcomes, as seen from the N-Gain Score for independent attitudes of 0.6 in the ‘moderate’ category and a percentage of 63% in the ‘quite effective’ category. The N-Gain Score for student learning outcomes was 0.5 in the “moderate” category with a percentage of 58% in the ‘quite effective’ categories.